Interactive determination by total metals in waters of the inner Puno bay of Lake Titicaca (Peru) - Moreno Terrazas, Edmundo (2017)
The inner Puno bay is a restricted area and one of the habitats of Lake Titicaca with high anthropization, where some organic and inorganic elements may be exceeding the thresholds allowable concentrations. The aim of the research was to determine interactively total metals available in the waters of the inner Puno bay of Lake Titicaca, Peru. It was conducted between January and November 2016 by a non-probabilistic for convenience and applying the theoretical method by comparison among six stations of selection. Cu, Zn, Pb, Cd,As, Hg were the determined and quantified elements using atomic absorption spectrometry by inductively coupled plasma with axial view (ICP-AES). It was observed that between the stations there were no statistically significant differences (p ≤ 0.05) when there was an availability of exposure among all the elements, although when comparing each element per station, there were differences for the rainy (January-February-March) and dry season (September-October-November). By comparing each station and between seasons, we found that there was no statistically significant difference, although the higher concentration levels were for the dryness season. We conclude that there is environmental exposure by metals in the waters of the Inner Bay and where their concentrations are permanent during the whole period of the year, being able to bring negative consequences not only for the ecosystem, but also to the human health itself given activities of community benefit that are developed in this geographic space.